2018
DOI: 10.1007/s40415-017-0435-7
|View full text |Cite
|
Sign up to set email alerts
|

First detection of species of the potentially toxic genus Azadinium (Amphidomataceae, Dinophyceae) in tropical coastal waters of Brazil

Abstract: In fall 1995, during a survey in Abrolhos coral reef system (southwestern Atlantic, Brazil), significant densities (143-6174 cells L-1) of small thecate dinoflagellates were detected. Analysis of this material in scanning and transmission electron microscopy confirmed the presence of four taxa assigned to the potentially toxic genus Azadinium: A. dexteroporum Percopo et Zingone, A. luciferelloides Tillmann et Akselman, A. cf. polongum Tillmann and Azadinium sp. The latter taxon showed external morphological fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Contrary to A. anophagefferens, A. dexeteroporum was detected throughout the year with the highest relative sequence abundances in January, February, and June. Based on the previous studies, the species can also grow in a wide temperature range (0.6 ˚C to 28˚C), depending on the geographic origin of the strain (Percopo et al 2013;Tillmann et al 2015Tillmann et al , 2020Cavalcante et al 2018). Furthermore, based on six years of weekly data analyzed by metabarcoding and HTS-approach, the species was detected throughout the year in the Sea of Okhotsk, from water temperatures of -1.7 ˚C to around 20˚C (Sildever et al 2019).…”
Section: Common/dominant/toxin-producing Species Appearance Patternsmentioning
confidence: 88%
“…Contrary to A. anophagefferens, A. dexeteroporum was detected throughout the year with the highest relative sequence abundances in January, February, and June. Based on the previous studies, the species can also grow in a wide temperature range (0.6 ˚C to 28˚C), depending on the geographic origin of the strain (Percopo et al 2013;Tillmann et al 2015Tillmann et al , 2020Cavalcante et al 2018). Furthermore, based on six years of weekly data analyzed by metabarcoding and HTS-approach, the species was detected throughout the year in the Sea of Okhotsk, from water temperatures of -1.7 ˚C to around 20˚C (Sildever et al 2019).…”
Section: Common/dominant/toxin-producing Species Appearance Patternsmentioning
confidence: 88%
“…; Cavalcante et al . ). In many areas of the world, the presence of Amphidomataceae is accompanied by the detection of AZAs (Taleb et al .…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, Az. luciferelloides has a wide distribution, ranging from cool slope Argentinean waters (Tillmann and Akselman 2016; present study) to tropical Brazilian waters (Cavalcante et al 2018). No cultured strain of the species is available yet, so its potential for AZA production is unclear.…”
Section: Azadinium Diversitymentioning
confidence: 87%
“…64-33.75;Akselman and Negri 2012), as well as during recent blooms on the external shelf and slope of El Rincón (temperatures 8-108C; Tillmann et al 2019). By contrast, in Brazilian coastal waters (temperatures 16-228S), Cavalcante et al (2018) found maximum Azadinium spp. (Az.…”
Section: Azadinium Diversitymentioning
confidence: 92%